Exploring the Social Economy and the Social Production of Housing Housing Cooperatives building spaces of resistance and transformation in Mexico City - Varnai, Bea (Premio Internacional de Tesis de Investigación sobre Vivienda y Desarrollo Sustentable 2015, 2015)
This research is interested in the Social Production of Housing (SPH), the main form of housing production in Mexico, and particularly in its organized modalities such as Housing Cooperatives (HC). It investigates their potential in providing affordable housing to low income sectors, as well as their broader social and political impacts by drawing on seven case studies located in the Federal District and established between the 1970s and 2015 in contrasting institutional contexts. They are analyzed through the lens of the Social Economy and the SPH that only recently is employed as an academic and analytical category. The research positions HC in the broader context of the retreat of the state and the emergence of the private sector as main actor in the housing production. Findings show that HC provide housing below market-value and carry a broader political project of social transformation that has to be, however, confronted with real-life practices.